First Report of Strawberry Leaf Blight Caused by Fusarium Fujikuroi Species Complex in Bangladesh (Journal of Bio-Science, 2023)
Strawberry leaf blight is one of the devastating fungal diseases, responsible for reducing the quality of strawberry production worldwide. The present experiment was conducted to determine the pathogenic fungal association with strawberry leaves obtained from the experimental site of Botanical Garden, Jahangirnagar University, Bangladesh. A fungal pathogen causing leaf blight disease of the strawberry plant was detected as Fusarium fujikuroi species complex through classical and molecular approaches. Molecular characterization showed that nucleotide sequences of the internal transcribed region of the studied fungus (MH368119.1) were genetically identical with Fusarium fujikuroi species complex. Different culture media, pH, light regimes, temperatures were assayed to know the growth pattern of the identified pathogenic fungus. The optimum vegetative growth of Fusarium fujikuroi species complex was recorded on Potato Dextrose Agar, Potato Sucrose Agar, and Honey Peptone Agar media, at 25°C temperature, pH seven and under complete dark conditions. Among the three antagonistic fungi for the assessment as a biocontrol agent, Trichoderma asperellum was comparative effective against Fusarium fujikuroi species complex under in vitro conditions. Among systemic chemical fungicides, the highest mycelial inhibition (89.42%) of the isolated fungus was found by Tilt 250 EC (500 ppm). The leaf blight of strawberry caused by Fusarium fujikuroi species complex is the new record in Bangladesh.J Bio-Sci. 30(1): 11-20, 2022 (June)